Comparison of Web 2.0 Use on State University Websites in Indonesia and Top World Universities Related to Webometric Ranking - Handaru Jati (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2022)
The present work determines the presence in the web 2.0 that twenty universities had through their educational portals. The universities are selected according to the Webometrics ranking (the ten best located in Indonesia and the best located worldwide) to identify what Web 2.0 tools they use. This study explores the educational portals of the twenty selected universities to determine which Web 2.0 tools they use and variables of the tools found will be assessed. The study only considers those Web 2.0 tools which are linked to the websites of universities. Of the two most used tools, the relevant indicators are quantified from Youtube